Overcoming immunotherapy resistance in gastric cancer: insights into mechanisms and emerging strategies - Dingtian Luo; Jing Zhou; Shuiliang Ruan; Binzhong Zhang; Huali Zhu; Yangming Que; Shijie Ying; Xiaowen Li; Yuanmin Hu; Zhengwei Song (Cell Death and Disease)
Abstract Gastric cancer (GC) remains a leading cause of cancer-related mortality worldwide, with limited treatment options in advanced stages. Immunotherapy, particularly immune checkpoint inhibitors (ICIs) targeting PD1/PD-L1, has emerged as a promising therapeutic approach. However, a significant proportion of patients exhibit primary or acquired resistance, limiting the overall efficacy of immunotherapy. This review provides a comprehensive analysis of the mechanisms underlying immunotherapy resistance in GC, including the role of the tumor immune microenvironment, dynamic PD-L1 expression, compensatory activation of other immune checkpoints, and tumor genomic instability. Furthermore, the review explores GC-specific factors such as molecular subtypes, unique immune evasion mechanisms, and the impact of Helicobacter pylori infection. We also discuss emerging strategies to overcome resistance, including combination therapies, novel immunotherapeutic approaches, and personalized treatment strategies based on tumor genomics and the immune microenvironment. By highlighting these key areas, this review aims to inform future research directions and clinical practice, ultimately improving outcomes for GC patients undergoing immunotherapy.